Solution of fractional vibration equation by the variational iteration method and modified decomposition method - Das S. (My University, 2025)
In the present paper, the solutions of the fractional vibration equation for very large membranes are obtained with the help of two powerful methods, the variational iteration method and a modified decomposition method. Both methods perform extremely well in terms of efficiency and simplicity. Numerical results are presented graphically.